2020
DOI: 10.4049/jimmunol.204.supp.66.20
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal IgE antibody secreting cell (ASC) repertoire analysis suggests an extrafollicular developmental program

Abstract: Allergic fungal rhinosinusitis (AFRS) is a subset of chronic rhinosinusitis with nasal polyposis (CRSwNP). AFRS is primarily associated with a type 2 inflammatory profile including eosinophilic mucosal infiltration and high serum and mucosal titers of IgE. Patients with AFRS have increased frequencies of IgE ASCs within NP structures, although it is unclear if these cells originate from a germinal center (GC) reaction or undergo local mucosal extrafollicular differentiation and class switch recombination (CSR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…IgE targeting nasal pathogens such as Staph. aureus [27], autoantigens [28 ▪ ,29,30,31] fungal antigens [32 ▪▪ ] as well as allergens more typically associated with allergic disease [33,34 ▪ ] have all been identified. While this suggests that there may be different antigenic triggers of IgE responses at the individual level, it confirms that the dysregulation of B cell responses results in the local production of antigen-specific antibodies that drives the pathogenesis of CRSwNP through Fc-dependent effector mechanisms.…”
Section: Chronic Rhinosinusitis With Nasal Polyps and B Cell Derived ...mentioning
confidence: 99%
See 1 more Smart Citation
“…IgE targeting nasal pathogens such as Staph. aureus [27], autoantigens [28 ▪ ,29,30,31] fungal antigens [32 ▪▪ ] as well as allergens more typically associated with allergic disease [33,34 ▪ ] have all been identified. While this suggests that there may be different antigenic triggers of IgE responses at the individual level, it confirms that the dysregulation of B cell responses results in the local production of antigen-specific antibodies that drives the pathogenesis of CRSwNP through Fc-dependent effector mechanisms.…”
Section: Chronic Rhinosinusitis With Nasal Polyps and B Cell Derived ...mentioning
confidence: 99%
“…Naïve B cells comprise the most abundant B cell subset in peripheral blood, whereas in NP there are relatively higher proportions of plasmablasts and memory B cells (both switched and unswitched). A recent study [32 ▪▪ ] reported that the majority of antibody secreting cells in NP have a double negative phenotype (IgD − CD27 − ), which are typical of extrafollicular responses. Consistent with this, a previous study [36 ▪▪ ] found that NP plasmablasts express high levels of EBI2, a marker associated with extrafollicular B cell responses.…”
Section: Immunoglobulin Excessmentioning
confidence: 99%
“…IgE + ASC have been identified in several tissues by flow cytometry, most notably, in peripheral blood and in nasal polyps, which is associated with local IgE production and detection of target antigens in the tissue 38,128,186–188 . Transcriptomically validated IgE + ASC have been detected in peripheral blood of individuals with atopic diseases, 38,39 in dissected polyps from individuals with allergic rhinitis with nasal polyps, and intestinal mucosa of peanut allergic individuals 127,189–191 (Figure 6). Transcriptome analysis of IgE + ASC suggest that the bulk resolvable IgE + ASC are plasmablasts or immature ASC, rather than mature plasma cells, as they maintain expression of MHC‐II, a marker that is down‐modulated in the first few days after ASC obtain quiescence 38,125,191 .…”
Section: The Life Spans Of Ige+ Ascmentioning
confidence: 99%
“…Transcriptomically validated IgE + ASC have been detected in peripheral blood of individuals with atopic diseases, 38,39 in dissected polyps from individuals with allergic rhinitis with nasal polyps, and intestinal mucosa of peanut allergic individuals 127,189–191 (Figure 6). Transcriptome analysis of IgE + ASC suggest that the bulk resolvable IgE + ASC are plasmablasts or immature ASC, rather than mature plasma cells, as they maintain expression of MHC‐II, a marker that is down‐modulated in the first few days after ASC obtain quiescence 38,125,191 . Interestingly, one study showed that IgE + ASC lost expression of MKI67 , a marker of the proliferative plasmablast state, suggesting that IgE + ASC can become quiescent 191 .…”
Section: The Life Spans Of Ige+ Ascmentioning
confidence: 99%
See 1 more Smart Citation